Fabrication of dielectric Ba2Ti9O20 ceramic by a polymerized complex method - (:unkn) unknown (My University, 2009)
Fabrication of Single phase Ba2Ti9O20 ceramic using the solid state reaction method is rather difficult due to thermodynamically various stable compounds that form in the vicinity of Ba 2Ti9O20 composition. In this study, microwave dielectric Ba2Ti9O20 ceramic was successfully prepared by a polymerized complex method where crystallization Of Ba 2Ti9O20 occurred from an amorphous polymeric mixture. Calcined powders had a particle size ranging from 10 to 50 nm with spherical shape. Single phase Ba2Ti9O20 ceramic was obtained at 1200°C. The dielectric constant Of Ba2Ti 9O20 ceramics at room temperature was around 34.5 at frequencies above 250 kHz but it significantly decreased when temperature was above 25°C.
Keywords: Ba2Ti9O20; Microwave dielectrics ceramics; Polymerized complex method